Jonah and the meaning of our lives : a verse-by-verse contemporary commentary - Bob, Steven M., 1950- (Philadelphia : Jewish Publication Society ; Lincoln : University of Nebraska Press, 2016)
"The Book of Jonah stands unique among the biblical books of the prophets because it is almost entirely narrative. And, in contrast to all the other prophets portrayed as admirable individuals who bravely speak God s word, Jonah stands out as flawed and fleeing from God. We are drawn to Jonah because God gives him an opportunity to redeem himself. His experience inspires us to find our own second chances and our own paths to meaningful growth."--publisher's website
41 The Fred Bob Principle: What Circumstances Will Lead to Success?42 Bringing Water to Our Lives: Do We Appreciate Those Who Help Us?; 43 Seeing Evil: Can We Recognize Our Own Flaws?; 44 Playing a Part: How Do We Shape the Narrative of Our Lives?; 45 Getting Lost: How Do We Regain Our Path?; 46 Narcissism: What Is Our Place in the World?; 47 Connecting the Dots: How Can We Make Sense of Our Lives?; 48 The Kikayon: What Can We Learn from a Plant?; 49 Time, Time, Time: How Do We View the Length of Our Lives?; 50 Facing Challenges: How Do We Use Our Strengths to Overcome Our Weaknesses?
Master record variable field(s) change: 072
Keywords: Bible. -- Criticism, interpretation, etc; Bible; RELIGION / Biblical Studies / Prophets; RELIGION / Judaism / Sacred Writings; Criticism, interpretation, etc; Electronic books